Anti-chromatin antibodies in juvenile rheumatoid arthritis - F. Ingegnoli; N. Del Papa; E. Lupi; D.P. Comina; W. Maglione; V. Gerloni; F. Fantini (PAGEPress Publications, 2003)
Objective: to evaluate the prevalence and clinical significance of anti-chromatin antibodies (Abs) in juvenile rheumatoid arthritis (JRA). Methods: IgG anti-chromatin Abs were detected by an enzyme-linked immunosorbent assay (ELISA), in sera of 94 children with JRA (10 children with systemic, 38 with polyarticular and 46 with oligoarticular disease onset). As control group, 33 age- and-sex-matched healthy children (HC) were also examined. Results: Abs to chromatin were detected in 24/94 (25,5%) of children suffering from JRA. Particularly, the higher prevalence of anti-chromatin Abs has been found in children with oligoarticular (30,4%) and polyarticular (23,7%) onset JRA. In these groups Abs titers were significantly higher compared to systemic JRA and HC (p=0.003). Anti-chromatin Abs were observed more frequently in patients with oligoarticular disease and chronic uveitis (21,7%). Furthermore, higher levels of anti-chromatin Abs has been found in all the patients treated with anti-TNFα therapy (p<0.0001). Conclusions: our results confirm previous data about the prevalence of anti-chromatin Abs in JRA. These Abs were significantly higher in the group of patients with oligoarticular onset with past or present hystory of ocular involvement and in the group with polyarticular JRA treated with biologic therapy. A long-term follow-up study could be useful to evaluate the potential utility of these autoantibodies.